Gonads and Gametes of South American Neotropical Species - de Siqueira-Silva, Diógenes Henrique; Rodrigues, Maira da Silva [UNESP]; Rodrigues, Jeane; Da Costa, Daniel Fernandes [UNESP]; Rosa-Silva, Maria Clara; Nóbrega, Rafael Henrique [UNESP] (Taylor & Francis, 2024)
Neotropical aquatic environments are undoubtedly a hotspot for fish species, as the Amazon region is recognized for sheltering the highest freshwater biodiversity in the world. However, as in any other part of the planet, its residents are facing a reduction in their natural population stocks, partly influenced by climate changes but mainly due to environmental anthropization, which includes the overexploitation of species by the extractives fishing and habitat degradation. The knowledge of the biology and physiology of those species are therefore of essential importance to mitigate their risk of extinction from their habitats. Since species reproduction is one of the main aspects that enable fish survival, studies describing fish reproductive biology are of major importance and are among the most performed by researchers. Concomitantly, the development of new methods and the improvement of the already established protocols for the cryopreservation of fish gametes may also ensure the species’ survival in case of their extinction from nature. This chapter discusses structural particularities in the gonads of Neotropical fish species and describes gametes morphology.